IMPLEMENTASI GERAKAN 1000 HARI PERTAMA KEHIDUPAN DI KABUPATEN PASAMAN 2017 [Implementation of The First 1000 Days of Life Movement in Pasaman Regancy 2017] - Nesra Nefy; Nur Indrawati Lipoeto; Edison Edison (Universitas Airlangga, 2019)
The fi rst 1000 days of life movement, is an effort to support the commitment to accelerate nutrition improvement plan action since pregnancy until the age of 2 years. Considering the high number of nutritional problems in the last 3 years, namely stunting, wasting, low birth weight, and anemia in pregnancy, we should reevaluate the implementation of The First 1000 Days of Life Movement in Kabupaten Pasaman. The aim of this research was to describe the input, process, and output. This study was a qualitative research, with problems the fi rst 1000 days movement indepth interview, document review, and observatio. There were 19 informants. The result of the study for the input aspect was there was no written regulation, no vision and mission, no program objectives, no commitment, and there was lack in human resources and infrastructures. The result from the process aspect of the movement is specifi c and sensitive intervention, and the result from the output aspect was there were still a couple of program objectives has not yet been achieved. The conclusion of this research is, there is still no written regulation and no optimization of multi sector involvement in the 1000 HPK movement, and there is also the lack of human resources and infrastructure. Specifi c and sensitive interventions have been done but there is still lack of monitoring and evaluation. The suggestion that can be proposed for Health Ministry as the leading sector that can promote the formation of regulation and commitment to The First 1000 Days of Life Movement.